A identidade e a memória como fatores de desenvolvimento e integração: a Quarta Colônia de Imigração Italiana do RS/Brasil e o desenvolvimento regional (1955-2020) - Cruz, Jorge Alberto Soares (2020)
The Fourth Colony of Italian Immigration is located in the central part of Rio Grande do Sul State. This territory occupation began in 1877, with the arrival of Russian-German immigrants, who abandoned the region due to a series of misfortunes. In early 1878, the first families of immigrants from northern Italy began to arrive. On account of the colony isolation, these groups developed a sense of belonging to an ethnic, identity, and religious culture, which is an outstanding feature in the region. In 1886, the colony had its territory divided into the municipalities of Santa Maria, Cachoeira do Sul, São Martinho, and Vila Rica. In the 50s and 60s, 20th century, under the leadership of the priest Luiz Sponchiado, an attempt to integrate the former colony around a common ideal was made. The parish priest sought to bring together the residents of the region by strengthening of Italian spirit and religiosity. However, due to political interests, the idea of unification proposed by the priest did not prevail, which led to the emergence of seven small municipalities: Nova Palma, Faxinal do Soturno, Dona Francisca, Silveira Martins, São João do Polêsine, Pinhal Grande, and Ivorá. In the 80s and 90s, the 20th century, the feeling of belonging to an ethnic group was revived in the Italian-Brazilian community of Santa Maria and the Fourth Colony, with the reopening of Italian societies, associations, and circolos, as well as the Italian Consular Agency. In addition, there was the development of heritage education projects that value regional history, culture, and tourism. After the political emancipations, in 1995 was created the CONDESUS (Consortium for Sustainable Development of the Fourth Colony), which has sought to overcome the delay in economic development caused by the fragmentation of the territory. A new Fourth Colony emerged from CONDESUS, with the annexation of the municipalities of Restinga Seca and Agudo. Therefore, the idea held is that the economic integration and the strength of a regional “bloc” are intimately linked to the valorization and promotion of the historical identity of the Fourth Imperial Colony of Italian Immigration at the Rio Grande do Sul State, which is the factor that aggregates and motivates regional development. It also seeks to demonstrate that the process of identity construction of the Fourth Colony territory enabled and established the political bases for the emergence of CONDESUS. So, to achieve the objectives a qualitative research was developed. In this context, two types of variables were listed: the Independent Variables that aggregate CONDESUS, the territory, the Consular Agency, the Italian associations and circolos, which are determinants in the research results, and influencers in the Dependent Variables that relate to memory, culture, identity, and regional development. Thus, it is concluded that historical, cultural, and identity factors are important in the context of the development of the Fourth Colony. However, just those elements will not have the potential to promote regional development, which must happen through the union of a set of factors.